The Factors That Cause a Publicly Listed Company in The Indonesian Stock Exchange to Be Given an Adverse Audit Opinion - Dheny Biantara; Levina Caroline; Safrida Rumondang; Iwan Lesmana (Journal of International Conference Proceedings, 2021)
This study aims to analyze the factors that cause the financial statement of a publicly listed company in the Indonesian Stock Exchange to be given an adverse audit opinion by the independent auditor in 2020. A financial statement is important to the users as a basis of decision-making. Hence, in order to assure whether or not the company’s financial information has been faithfully represented, companies are required to undergo the financial statement audit process where independent auditors will evaluate and state an audit opinion based on the assessment made during the audit process. The researcher uses the explanatory case study methodology to further understand the explanation for this phenomenon. The data used for this research is taken from the company’s financial statement and disclosure from 2018 to 2021. The data and results of this study have shown the presence of material findings in the company’s financial statement, which is not stated according to Indonesia’s generally accepted accounting principle (SAK), misuse of asset, as well as the violation of good corporate governance principles.